Fundamentals of Entrepreneurship (ENT300) Yummy Chai Kue... [et al.] - Farahin, Mospen; Abdul Wahab, Aziah; Mohd Saifuddin, Nur Syazwani; Suhaimi@Anggu, Eefi Nurannisha; Amira Natasha, Mohd Salleh; Nur Hafizah Rodhiyah, Rosman (2015)
The name of our company is Yummy Chai Kue . The business has been decided in the form of five partnerships. Each partner has contributed on an agreed amount of capital as in our agreement. Our main business activity is to serve various flavors of chai kue with set tea. We will be located at The Summer Mall, 94300 Kota Samarahan, Sarawak. Hopefully, we will be opened on 1st January 2017. All partners are entitled and encouraged to participate in all business management. All of us have agreed that Farahin Binti Mospen as the General Manager, Aziah Binti Abdul Wahab as an Administration Manager, Nur Syazwani Binti Mohd Saifuddin as a Marketing Manager and her assistant is Effi Nurannisha Bt Suhaimi, Amira Natasha Bt Salleh as the Operational Manager and Nur Hafizah Rodhiyah Bt Rosman, as the